Meningkatkan Nilai-Nilai Moderasi Beragama Di Lingkungan Mahasiswa - Aisya Huwayda; Aisyah Aulya Rahmawati; Esha Richwatun Azizah; Achmad Tubagus Surur (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Increasing the values ​​of religious moderation among students is an urgent need in facing the increasingly complex challenges of globalization and pluralism. This research aims to identify effective strategies in instilling and strengthening the values ​​of religious moderation in the campus environment. The method used is a qualitative approach with data collection techniques through interviews, observation and literature study. The research results show that character education, interreligious dialogue, and social activities involving various religious backgrounds can be effective means of increasing understanding and tolerance between students. Apart from that, the role of lecturers and student organizations is very important in creating an inclusive and harmonious campus atmosphere. In this way, it is hoped that strengthening the values ​​of religious moderation can form a young generation that is more tolerant, open and able to contribute positively to a pluralistic society. This research provides recommendations for the implementation of programs that support religious moderation as an integral part of the higher education curriculum.